Discoloration And Effectiveness Of Gafchromic EBT3 Film In Measuring Solar Ultraviolet Irradiance Using Spectroscopic Method - Osman,, Ummi Shuhada (2018)
Gafchromic External Beam Therapy 3 (EBT3) films were investigated for its ability to measure the ultraviolet (UV) irradiance (dose, in mJ/cm2) exposed directly to sunlight. Five different experiments were conducted by using different EBT3 films prepared to study the effectiveness of the films towards measuring solar UV irradiance using absorbance spectroscopy technique. Those films were exposed to the solar UV irradiance at various condition of sky, duration of time and places. The discoloration of the films is dependent on the exposure time, irradiance rate and condition of the sky.